Genetic Diversity and Prevalence of Giardia duodenalis in Qatar - Chourabi, Marwa; Boughattas, Sonia; Abdallah, Atiyeh M.; Ismail, Ahmed; Behnke, Jerzy M.; Al-Mekhlafi, Hesham M.; Abu-Madi, Marawan (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Giardia duodenalis is a common human intestinal parasite worldwide, and the causative agent of diarrhea, with the severity of disease ranging from asymptomatic to intense and debilitating infection. G. duodenalis is known to consist of eight genetically distinct assemblages, named from A to H. No data available on the genotypes and genetic diversity of G. duodenalis circulating in Qatar. Methods: We genotyped 54 human Giardia isolates, collected from asymptomatic immigrants in Qatar, using a multilocus genotyping (MLGs) tool. We also investigated relationships between the subjects’ genotypes and their demographic data. Results: Genomic DNA from 54 isolates were tested by PCR and sequence analysis at three loci: glutamate dehydrogenase (gdh), β-giardin (bg) and triose phosphate (tpi)). Assemblage A was identified in nine (16.67%), assemblage B in thirty (55.55%), and a mixture of assemblages A+B in fifteen (27.78%) isolates. All assemblage A isolates, genotyped in different loci, were assigned to sub-assemblage AII, and six of them had MLGs AII-1 while one new MLG was identified in two isolates. Sequences of assemblage B isolates have high level of genetic diversity and high presence of heterogeneous peaks, especially within the gdh gene. No significant associations between genotypes and the immigrants’ demographic data were found due to the extensive number of new variants. Conclusions: MLGs was used herein to genotype 54 immigrant Giardia isolates. The high level of genetic variability found in our isolates hampered MLGs determination, more investigations are now required to consolidate our findings, and to enable a comprehensive understanding of the diversity within G. duodenalis assemblage B isolates.